A trial of integrated buprenorphine/naloxone and HIV clinical care. - Sullivan, Lynn E; Barry, Declan; Moore, Brent A; Chawarski, Marek C; Tetrault, Jeanette M; Pantalon, Michael V; O'Connor, Patrick G; Schottenfeld, Richard S; Fiellin, David A (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2006)
Untreated opioid dependence adversely affects the care of human immunodeficiency virus (HIV)-positive patients. Buprenorphine, a partial opioid agonist, is available for maintenance treatment of opioid dependence in HIV specialty settings. We investigated the feasibility and efficacy of integrating buprenorphine, along with 2 levels of counseling, into HIV clinical care.
Keywords: Administration, Sublingual; Adult; Antiretroviral Therapy, Highly Active; Buprenorphine; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Follow-Up Studies; HIV Infections; Humans; Male; Middle Aged; Naloxone; Narcotic Antagonists; Opioid-Related Disorders; Pilot Projects; Probability; Reference Values; Risk Factors; Treatment Outcome